THE EFFECT OF BILINGUALISM ON CHILDREN'S INTELLIGENCE LEVEL - Lutfi Nurhayati; Elva Elfiani Salsa; Ichsan Fauzi Rachman (Media Inovasi Pendidikan dan Publikasi, 2024)
This research discusses the influence of bilingualism on children's intelligence levels. The method used in this research is the literature study method. The data collection technique used is looking for sources from various sources such as books, journals, articles, papers and previous research. Bilingualism is a common phenomenon amidst the current flow of globalization. Bilingualism has become a necessity in today's interconnected world for various educational, career or social interaction needs. Language is related to cognitive development. Based on the results of this literature study, it can be concluded that bilingualism is the ability to understand and use two or more languages ​​by a person. Bilingualism has more positive impacts on children's intelligence than negative impacts. Children who study bilingualism have better intelligence than those who only study monolingualism, this is shown by the abilities of bilingual children in abstract thinking, cognitive flexibility, and tolerant abilities as well as strong metalinguistic abilities.